The Implementation of Cooperative Integrated Reading and Composition (CIRC) Method in Teaching Narrative Text to Improve Students’ Reading Comprehension at the Eleventh Grade Students of MAN 2 Model Makassar - Darmayanti Darmayanti (Ethical Lingua: Journal of Language Teaching and Literature, 2014)
This study is aimed to improve the reading comprehension of eleventh grade students at MAN 2 Model Makassar by using CIRC Method. CIRC Method is chosen to practice the communication in the target language. The research problems are: (1). Does the use of CIRC method improve reading comprehension of the eleventh grade students of MAN 2 Model Makassar? (2). Are the students interested in teaching Narrative text through CIRC method of the eleventh grade students of MAN 2 Model Makassar? The objectives of the research were (1) to find out whether or not the use of CIRC method can improve reading comprehension of the eleventh grade students of MAN 2 Model Makassar. (2) to find out the students’ interest toward teaching Narrative text through CIRC method. The research applied Quasi-experimental Design. The population of the research was the Eleventh Grade students of MAN 2 Model Makassar in academic year 2013/2014. The sample was IPS 2 as Experimental Group consisting of 33 students and IPA 2 as Control Group consisting of 37 students, with the total sample 70 students. The researcher used Cluster Random Sampling, two classes of the eleventh grade of MAN 2 Model Makassar were took as the experimental class and the control class. The experimental class taught by using CIRC Method while the control class taught by conventional learning method. The data were collected through reading tests namely Pre test and Post test, that were analyzed by using SPSS 20.0 version. The result of the data showed that there was significant difference between the students’ score who were taught CIRC method and non CIRC method. It proven by the mean score of the experimental group that was higher than control group in the post test. The result of the test indicated that using CIRC method significantly improved the students’ reading comprehension. Then, the questionnaires were analyzed by using Likert Scale that showed the students were interested in learning English through CIRC Method. The findings of this study indicated that the implementation of CIRC Method has improved the students’ reading comprehension.